Influence of nickel citrate in flame retardant thermoplastic polyurethane elastomer composites based on ammonium polyphosphate - X. L. Chen; K. Wang; Y. X. Gu; C. M. Jiao; H. J. Liang; S. X. Li (eXPRESS Polymer Letters)
In this work, nickel citrate (NC) was combined with ammonium polyphosphate (APP) to improve the flame retardance of thermoplastic polyurethane (TPU). And, the influence of nickel citrate on the flame retardance of TPU/APP composites was investigated by cone calorimeter test (CCT), thermogravimetric analysis/infrared spectrometry (TG-IR), scanning electron microscope (SEM), gas chromatography/mass spectrometry (GC-Ms), and X-ray photoelectron spectrometer (XPS), respectively. It has been found the combination of NC and APP improved the flame retardancy and reduced the total heat release (THR) of TPU composites. The THR value of TPU/APP/NC0.5 was reduced by 20.7% at 750 s compared with that of TPU/APP. The flame retardancy of TPU composites and the graphitization degree of char residue from TPU composites were improved by the combination of both NC and APP. This work provided a new way to improve the flame retardancy of polymer composites.